2015
DOI: 10.1111/jmg.12155
|View full text |Cite
|
Sign up to set email alerts
|

Provenance of the HPHT subducted margin in the Variscan belt (Cabo Ortegal Complex, NW Iberian Massif)

Abstract: The Variscan Upper Allochthon is a continental-affinity terrane that recorded a Cambrian-Ediacaran magmatic arc generation, a subsequent transition to a passive margin, and a collision-related high-P metamorphism during the Devonian-Carboniferous amalgamation of Pangea. The objective of this article is to decipher which continental margin subducted in the Devonian high-P-high-T (HP-HT) event. To do so, a provenance study is presented using combined U-Pb (n = 613) and Lu-Hf (n = 463) isotopic LA-ICP-MS zircon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 105 publications
(169 reference statements)
1
12
0
Order By: Relevance
“…Moreover, the pre-Variscan crust of the FMC is dominated by paragneisses (and meta-granitoids derived from melting of the latter) corresponding to former sediments of the north Gondwana margin, which are characterized by Archean (2.5-3.3 Ga), Paleoproterozoic (1.8-2.2 Ga) and Neoproterozoic (0.5-0.7 Ga) detritus, as indicated by age patterns of detrital zircon grains (Albert et al, 2015;Linnemann et al, 2014). Fig.…”
Section: Mechanism Of Mantle Enrichment and Nature Of The Metasomaticmentioning
confidence: 99%
“…Moreover, the pre-Variscan crust of the FMC is dominated by paragneisses (and meta-granitoids derived from melting of the latter) corresponding to former sediments of the north Gondwana margin, which are characterized by Archean (2.5-3.3 Ga), Paleoproterozoic (1.8-2.2 Ga) and Neoproterozoic (0.5-0.7 Ga) detritus, as indicated by age patterns of detrital zircon grains (Albert et al, 2015;Linnemann et al, 2014). Fig.…”
Section: Mechanism Of Mantle Enrichment and Nature Of The Metasomaticmentioning
confidence: 99%
“…This interpretation is clearly confirmed at present by the existence in those complexes of a group of different ophiolitic units (Arenas and Sánchez Martínez, 2015;Arenas et al, 2018) and a pair of successive high-P metamorphic events dated at c. 400 and 370 Ma (Ordóñez Casado et al, 2001;Fernández-Suárez et al, 2007;Abati et al, 2010;Arenas et al, 2014;Díez Fernández et al, 2016). Several works have confirmed that the Ava-lonian-African margin of Gondwana has been an active margin for a long time, at least between 750 and 500 Ma, the Avalonian-Cadomian arc (Rodríguez- Pereira et al, 2006;Linnemann et al, 2008Linnemann et al, , 2014von Raumer and Stampfli, 2008;Fuenlabrada et al, 2010;Albert et al, 2015a, 2015b, von Raumer et al, 2015Andonaegui et al, 2016). According to this interpretation, the Central Iberian Zone very likely represents a back-arc basin located behind the most active part of the margin (Fernández-Suárez et al, 2014;Albert et al, 2015a;Orejana et al, 2015;.…”
Section: Discussionmentioning
confidence: 73%
“…The structurally lower imbricated thrust system hosts the Almendra Formation (Vacas and Martínez Catalán, 1987) which is a calciturbidite made of phyllite and calcarenite rhythms up to several meters thick . Local lenses of polygenic conglomerates and microconglomerates holding exotic clasts and pebbles, and lithified intraclasts were firstly described by Aldaya et al (1976). Their lithologies include phyllite, sandstone, litharenite, quartzite, limestone, orthogneiss, rhyolite and felsic volcanic tuff (Fig.…”
Section: Geological Settingmentioning
confidence: 99%
“…6d and e). The most consolidated sedimentary fragments suggest that they were recycled within the basin, as a wild flysch (Ribeiro and Ribeiro, 1974;Aldaya et al, 1976;González Clavijo and Martínez Catalán, 2002;. These fragments were considered a proof of its synorogenic character, and also evidence that the basin was fed from areas of the Variscan belt already deformed and metamorphosed (Antona and Martínez Catalán, 1990;González Clavijo and Martínez Catalán, 2002;Martínez Catalán et al, 2004, 2008.…”
Section: Magmatic Zircon Ages Of the Lpa Olistolithsmentioning
confidence: 99%